Case report: Salvage capmatinib therapy in KIF5B-MET fusion-positive lung adenocarcinoma with resistance to telisotuzumab vedotin - Lin, Chien-Yu; Wei, Sheng-Huan; Chen, Yi-Lin; Lee, Chung-Ta; Wu, Shang-Yin; Ho, Chung-Liang; Pavlick, Dean C.; Su, Po-Lan; Lin, Chien-Chung (Frontiers in Oncology, 2022)
Telisotuzumab vedotin is a MET-targeting antibody–drug conjugate that has demonstrated a good treatment response in patients with EGFR wild-type MET-overexpressing non-squamous non-small cell lung cancer. However, patients have been reported to acquire resistance to this drug, and the subsequent therapy has not been standardized. Here, we present a case of a 56-year-old woman diagnosed with KIF5B-MET fusion-positive non-small cell lung cancer who had a durable response to capmatinib after acquired resistance to telisotuzumab vedotin.